Trianthema portulacastrum Linn. (Bishkhapra) - Shivhare, Manoj K.; Singour, P. K.; Chaurasiya, P. K.; Pawar, Rajesh S. (Pharmacognosy Reviews, 2012)
World Health Organization (WHO) has recommended that traditional health and folk medicine systems are proved to be more effective in health problems worldwide. Trianthema portulacastrum Linn. is a herb used in Ayurvedic medicine. The principal constituent of T. portulacastrum Linn. is ecdysterone and the other constituents are trianthenol, 3-acetylaleuritolic acid, 5,2-dihydroxy-7-methoxy-6,8-dimethylfl avone, leptorumol, 3,4-dimethoxy cinnamic acid, 5-hydroxy2-methoxybenzaldehyde, p-methoxybenzoic acid, and beta cyanin. Different parts of Trianthema portulacastrum Linn. are traditionally used as analgesic, stomachic, laxative, treatment of blood disease, anemia, infl ammation, and night blindness. Laboratory investigations on extracts of the plant have demonstrated signifi cant pharmacological activities, such as antioxidant, diuretic, analgesic, hepatoprotective, and anticarcinogenic. This article compiles all updated information related to T. portulacastrum Linn. Scientifi cally proved activities are co-related with traditional concepts. Scientifi c evidence exists with respect to their major and minor constituents. The novelty and applicability of T. portulacastrum are hidden. Such things should be overcome through modern scientifi c concepts.
Keywords: Azoaceae; phytochemistry; pharmacological properties; Trianthema portulacastrum; traditional medicine